Local Culinary Travel Pattern Development Model in Lerep Tourism Village - Setiawan Wibowo; Nur Farah Fajriaty Muchlis; Muhammad Yahya (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2023)
This study aims to create a model for the development of the Local Culinary Travel Pattern in mapping the tourist segment who likes traditional food types and preparations using the Storynomics Tourism approach as a determinant of steps to enjoy regional culinary specialties. The research method used is qualitative using in-depth interview techniques with village officials, visiting tourists and local communities in the Lerep Tourism Village, Semarang Regency with field observation activities and literature review. The results of this study can develop culinary tourism activities that are packaged with traditional culinary markets in Lerep Tourism Village using the development model of a local culinary travel pattern based on local wisdom which is transformed into a menu of traditional creations from the community in synergy with views for tourism actors and potential tourists to determine activities culinary tourism trips that focus on local food as a cultural characteristic of an area.